ANALISIS COMMON SIZE STATEMENT DALAM MENILAI KINERJA KEUANGAN PT. CHAROEN POKPHAND INDONESIA, TBK DI BURSA EFEK INDONESIA - Hesti Sulistiyorini (Jurnal Akuntansi Indonesia, 2019)
Abstract : The purpose of this study is to analyze the financial performance of PT Charoen Pokphand Indonesia, Tbk using Common Size Statement analysis. This quantitative descriptive research uses the case study method. By using secondary data in the form of documentation of the company's financial statements for a period of 5 years taken from the Indonesia Stock Exchange. The results showed that the short-term financial condition, seen from the company's current assets and current debt, tended to decrease, indicating that the company was quite effective in managing its current assets and the short-term liabilities that the company had to bear were getting lighter. The level of sales that tends to increase indicates that the company is efficient in stabilizing the company's business activities. Long-term financial conditions show that the value of fixed assets tends to increase and total equity has a much higher percentage value than the percentage of debt. This shows that there is a guarantee from the company in the form of fixed assets that can be used to support the company's operational activities as well as a guarantee from its own capital to fund its fixed assets. And in the condition of the results of the business shows that the percentage of net income tends to decrease as well as the level of company sales which tends to increase this is due to the tendency of an increase in the company's cost of goods sold. This condition shows that the company has not been able to control the cost of goods sold and operating expenses which have an impact on reducing net income from its business activities. With this, it is hoped that the company will be able to stabilize its business activities by utilizing existing capital and controlling costs incurred by the company. Keywords: company financial statements, financial performance, common size statement